Analysis of the Metabolic Profile and Biological Activity of Hawthorn Species twigs: Crataegus azarolus and Crataegus monogyna - Qalatobzany, Hiwa Sheikh Ahmed; Muhammad, Kadhm Abdullah; Lateef, Djshwar Dhahir; Rasul, Kamaran Salh; Ibrahim, Abdulrahman Smail; Parreira , Mariana Casari; Weisany, Weria (Kurdistan Journal of Applied Research, 2025)
All parts of the hawthorn tree (Crataegus spp.), including fruits, flowers, and leaves, have been used as a source of bioactive compounds. Thus, in this investigation, the twigs of two species of hawthorn plant of Crataegus azarolus (C. azarolus) and Crataegus monogyna (C. monogyna) were evaluated for bioactive compositions and biological activity (antioxidant and antimicrobial activities). To evaluate bioactive compositions, high-performance liquid chromatography (HPLC) was applied, and for biological activity, biochemical assays were performed. C. monogyna revealed a higher amount of total phenolic, total flavonoid, and total tannin contents compared to C. azarolus. The HPLC results indicated the highest amount of kaempferol (14.40%), catechin (17.70%), and gallic acid (25%) in twigs of C. azarolus, while the maximum quercetin (72%) compound was present in C. monogyna. C. monogyna exhibited higher antioxidant activity by 1,1-dizarophenyl-2-picrylhydrazyl (DPPH) (86.13%) and 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid (ABTS) (92.93%) compared to C. azarolus for antioxidant activity-DPPH (81.86%) and -ABTS (87.47%) assay. In the case of antimicrobial activity, the twigs of both species (especially C. azarolus) have a capacity against Bacillus subtilis, Staphylococcus aureus, and methicillin-resistant Staphylococcus aureus. The results of this study revealed that the twigs of both species contained a high amount of phenolic metabolites and antioxidant activity, while they showed low antimicrobial activity.